Proposed Reforms to the Exogenous Shocks Facility. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The review of the ESF is being accelerated in light of experience and worsening global economic conditions, in particular the surge in food and fuel prices. Despite having become effective in 2006, the ESF has yet to be used. Recent discussions with creditors, donors, potential users, and outside observers have highlighted a number of ways to enhance its effectiveness.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet